Rethinking the virtues from the critical analogical hermeneutics - Polo Santillán, Miguel Ángel (2017)
The article is a reflection about the possibilities of the ethics thought from the analogical hermeneutics, with critical sense. For this, we review the assumptions of analogical hermeneutics proposed by Mauricio Beuchot. From there we study the components of one theory of virtues, such as prudence. Then we discuss three classic topics: human nature, perfection and the distinction between public and private virtues. Finally, we think the virtues from the process of globalization.